Harnessing the Utility of Ex Vivo Patient Prostate Tissue Slice Cultures - Perez, Lillian M.; Nonn, Larisa (Frontiers in Oncology, 2022)
Patient-derived prostate tissue explant cultures are powerful research tools that offer the potential for personalized medicine. These cultures preserve the local microenvironment of the surrounding stroma but are not without limitations and challenges. There are several methods and processing techniques to culture tissue ex vivo, that include explant tissue chunks and precision-cut tissue slices. Precision-cut tissue slices provide a consistent distribution of nutrients and gases to the explant. Herein we summarize the prostate tissue slice method, its limitations and discuss the utility of this model, to investigate prostate biology and therapeutic treatment responses.